الادراكات العقلية ورفضها لمفهوم الفكر الالحادي - نفاوة, رغد فيصل; حسن, أرشد حمزة (Al-Adab Journal, 2019)
This study discussed the concept of mental perceptions as well as the concept of unilateralism which has become a widespread phenomenon in Iraqi society. This is clearly found among college students and some intellectuals who openly declare adopting these unacceptable destructive ideas. Here, government departments must stand up to this phenomenon as well as the role Which should be taken by the clerics in the fight against this extremist thought on the considerations that this thought is a threat to the doctrine and the entity of Iraqi society, and here came our choice of the subject of mental perceptions in the Koran and the fight against atheist thought. We have presented a critical study of the phenomenon of atheism, relying on a scientific methodology based on certainty, away from illusions and delusions. It is governed by the logical logical approach based on the Holy Quran, which carries the argument of implementing the idea of ​​atheism and emphasizing the existence of the divine self that governs the course of this vast universe.